Discovering the New Testament: An Introduction to Its Background, Theology, and Themes (Volume III: General Letters and Revelation) - Keown, Mark J. (Faithlife Corporation, 2022)
Intro -- Title Page -- Copyright -- Contents -- Abbreviations -- Introduction to Volume 3 -- Chapter 1: Hebrews -- Authorship -- Internal Clues -- Candidates -- Provenance and Date -- Recipients -- The Situation -- The Supremacy of Christ -- Christ over Prophetic Revelation -- Christ over the Angels -- Christ over Moses -- Christ over the Priesthood, Former Covenants, the Law, and Israel's Worship System -- Exhortation and Warning -- How Shall We Escape If We Neglect Such a Great Salvation? (Heb 2:1-4) -- Consider Jesus (Heb 3:1-4:16) -- Grow up in Christ or Face the Dreadful Consequences (Heb 5:11-6:12) -- Exhortation and Warning (Heb 10:19-39) -- Run the Race with Perseverance (Heb 12:1-29) -- Final Injunctions (Heb 13:1-19) -- Can a Real Believer Fall Away? -- The Use of the Old Testament in Hebrews -- Overall Message -- Key Old Testament Figures -- Israel's Traditions -- Specific Texts -- Hebrews 1:5-2:18 -- Hebrews 3:1-4:13 -- Hebrews 4:14-5:10 -- Hebrews 5:11-6:20 -- Hebrews 7:1-10:18 -- Hebrews 10:19-39 -- Hebrews 11:1-12:29 -- Hebrews 13:1-21 -- Summary -- Genre -- Hebrews as a Sermon -- Hebrews as Rhetoric -- Hebrews and Discourse Analysis -- Conclusion -- Structure -- Other Themes -- Angels -- Suffering and Temptation -- Faith -- The Divine and Human Christ -- The Deity of Christ -- The Humanity of Christ -- Questions to Consider -- Chapter 2: James -- The Catholic or General Epistles -- The General Epistles and the Canon -- Introduction to James -- Authorship -- Challenges to James the Brother of Jesus as Author -- The Case for James the Brother of Jesus -- Conclusion -- An Overview of James -- Date -- Provenance -- Recipients and Their Situation -- The Use of the Old Testament, the Gospels, and Other Sources -- The Old Testament -- The Gospel Traditions -- James' and Paul's Theologies of Justification -- Genre -- Structure.